STATUS AND DIVERSITY OF VESICULAR ARBUSCULAR MYCORRHIZA IN DIFFERENT AGE SERIES SPONGE IRON SOLID WASTE DUMPS WITH RESPECT TO RECLAMATION - B. KULLU,; N. BEHERA, (The Bioscan, 2012)
In the present study status and diversity of VAM fungi in different age series sponge iron solid waste dumps were investigated. The study revealed that the freshly laid dump (Do) was devoid of any VAM fungi. With increasing age of the waste dump VAM pore density gradual increased in 1, 3 and 5 years old dumps. A total of 35 VAM species belonging to 5 genera namely Glomus, Gigaspora, Acaulospora, Scutellospora and Sclerocystis were recorded, out of which 30 were noted in waste dumps. It was also found that Glomus and Acaulospora were present in high density. Glomus mosseae was found to be dominant species with highest relative spore density. Species richness and diversity index showed increasing trend with the dump age. It was concluded that VAM fungi adapted in waste dumps can be used for successful reclamation programme.